Comparison between GNSS ground-based and GPS radio occultation precipitable water observations over ocean-dominated regions - Burgos Fonseca, Yuditsabet (2018)
Precipitable water (PW) inferred from GPS (Global Positioning System) radio occultation (RO) and ground-based (GB) Global Navigation Satellite System (GNSS) observations are compared between years 2007 and 2014. As previous studies were mainly performed over continental areas we now focus over ocean-dominated geographical areas. Our analysis is done in order to find out how the reliability level of RO results over oceanic areas compares to land. As RO soundings usually miss some information close to the ground, we also assess different methods to complete the lacking data. We found 47 terrestrial stations that lie in islands small and far away from continental areas where the weather might be governed by the sea conditions. From comparisons of almost 5000 collocated samples, PW from RO and GB exhibit a global mean difference around 1 mm, root-mean-square deviation about 5 mm and a correlation above 0.9. The 2007–2014 timeseries and the monthly mean RO and GB PW were also compared to reanalyses per hemisphere, latitude regions and oceans. In each zone it was found that PW from RO, GB and reanalyses all exhibit in general consistent seasonal qualitative behavior. However, quantitative differences exist between reanalyses on one side and RO and GB on the other side. It is shown that PW from reanalyses lacks reliability in areas where the island topography is poorly represented by them. We also conclude that RO and GB seem to be more sensitive for the detection of features that depart from the regular annual cycle.